335 Improvement in sleep quality, anxiety and depression in adults with moderate-to-severe atopic dermatitis with dupilumab treatment. (25th January 2023) - Merola, Joseph F; Chiou, Albert S; During, Emmanuel; Costanzo, Antonio; Foley, Peter; Ardeleanu, Marius; Wu, Jiangming; Ozturk, Zafer E
Abstract: Sleep disturbance is considered one of the most prevalent symptoms of atopic dermatitis (AD), and is associated with daytime sleepiness, anxiety and depression. In previous phase 3 trials, dupilumab treatment demonstrated significant improvement in objective AD signs and severity of symptoms, including sleep disturbance and mental health symptoms. To investigate the effect of dupilumab for up to 24 weeks on sleep quality, daytime sleepiness, anxiety and depression, using data from the DUPISTAD (NCT04033367) study. The randomized, phase 4 DUPISTAD study, was divided into two 12-week periods: an initial double-blind placebo-controlled period, and a subsequent 12-week open-label extension (OLE) period. The 24-week study enrolled adult patients with moderate-to-severe AD (Eczema Area and Severity Index score ≥12, Peak Pruritus Numeric Rating Scale [NRS] score ≥3, Sleep Disturbance NRS average score ≥5) who showed an inadequate response to topical treatments. These patients were randomized 2 : 1 to dupilumab 300 mg every 2 weeks (q2w) for both the double-blind and OLE periods or placebo for the initial double-blind period, followed by dupilumab 300 mg q2w for the OLE period. The use of concomitant topical corticosteroids was permitted as needed by both groups throughout the study. Endpoints included mean change from baseline to week 24 for Patient-Reported Outcome Measures Information System (PROMIS) Sleep T-score (standardized score ranging from 30 [best] to 80 [worst], with a mean of 50), Epworth Sleepiness Scale (ESS; scored 0–24; higher values indicate increased daytime sleepiness), and Hospital Anxiety and Depression Scale (HADS; scored 0–21; higher values indicate a worse outcome). Throughout the study, patients also completed a Sleep Diary, recording the NRS of restfulness upon waking up (scored 0–10; lower values indicate a worse outcome). Statistical comparisons were not performed on the data collected during the OLE observation period. A total of 188 patients were enrolled in the study: 127 received continuous dupilumab (dupilumab–dupilumab group) and 61 received placebo to week 12 and then dupilumab to week 24 (placebo–dupilumab group). Baseline demographics and disease characteristics were well balanced. Improvement from baseline in sleep quality, daytime sleepiness, anxiety and depression was observed at week 24 in both groups, as illustrated by the mean change from baseline in PROMIS Sleep T-scores (−12.5 in the dupilumab–dupilumab group and −11.7 in the placebo–dupilumab group), ESS scores (−4.6 in the dupilumab–dupilumab group and −3.7 in the placebo–dupilumab group), HADS anxiety scores (−3.8 in the dupilumab–dupilumab group and −4.4 in the placebo–dupilumab group), HADS depression scores (−4.4 in the dupilumab–dupilumab group and −3.4 in the placebo–dupilumab group), and the NRS of restfulness upon a waking-up item of the Sleep Diary (+3.3 in the dupilumab–dupilumab group and +3.4 in the placebo–dupilumab group). The improvement achieved by the placebo–dupilumab group converged with that of the dupilumab–dupilumab group during the OLE period, as shown by the mean change from week 12 to week 24 in PROMIS Sleep T-score (−3.8), ESS score (−1.9), HADS anxiety score (−1.6), HADS depression score (−0.9) and NRS of restfulness upon a waking-up item of the Sleep Diary (+1.5). The safety profile of dupilumab was consistent with the known safety profile. Dupilumab provided sustained improvement through 24 weeks in patient-reported measures of sleep, daytime sleepiness, anxiety, and depression in adult patients with moderate-to-severe AD. Patients who were switched from placebo to dupilumab at week 12 showed rapid improvement in these parameters after the switch, eventually matching the improvement achieved by patients who received dupilumab from baseline through week 24.